2018
DOI: 10.1115/1.4038780
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Iodine-Doped Carbon Nanotube Conductors

Abstract: The widespread use of copper in power and data cabling for aircraft, ships, and ground vehicles imposes significant mass penalties and limits cable ampacity. Experimental research has suggested that iodine-doped carbon nanotubes (CNTs) can serve as energy efficient replacements for copper in mass sensitive cabling applications. The high computational costs of ab initio modeling have limited complimentary modeling research on the development of high specific conductance materials. In recent research, the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Included within these processes is the need to functionalize the CNTs to both increase their conductivities and minimize the interfacial resistance between them. 6,7 The process-dependent variability in both of these areas, further coupled with the different types of CNTs that can be employed for conductor fabrication, is responsible for the wide range of resistivity values reported in the literature for various conductor approaches. 5,8−14 Many approaches for full or partial replacement of traditional engineering materials have been demonstrated with CNTs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Included within these processes is the need to functionalize the CNTs to both increase their conductivities and minimize the interfacial resistance between them. 6,7 The process-dependent variability in both of these areas, further coupled with the different types of CNTs that can be employed for conductor fabrication, is responsible for the wide range of resistivity values reported in the literature for various conductor approaches. 5,8−14 Many approaches for full or partial replacement of traditional engineering materials have been demonstrated with CNTs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Technologically useful conductors will require material forms where the CNTs are highly aligned and tightly packed together to maximize the amount of active or connected interfacial area within a conductive assembly. Included within these processes is the need to functionalize the CNTs to both increase their conductivities and minimize the interfacial resistance between them. , The process-dependent variability in both of these areas, further coupled with the different types of CNTs that can be employed for conductor fabrication, is responsible for the wide range of resistivity values reported in the literature for various conductor approaches. , …”
Section: Introductionmentioning
confidence: 99%
“…The other essential modeling inputs are a geometry model for the "nanowire" and scaling information, since the quantum calculations are made at the nanoscale. This subsection extends previous work 13 (focused on CNT-based nanowires) to the GNR-based nanowire case, adopting the simplest possible set of geometric and scaling assumptions needed to estimate the macroscale (experimentally measured) performance of doped graphene-based conductors. The nanowire modeling results are presented in the form of an expected macroscale performance range, recognizing that macroscale carbon conductors consist of bundles or assemblies of nanowires, as opposed to a uniform crystal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Only 6-zGNR junctions were modeled at the higher of the two doping densities discussed in the preceding section. Previous modeling work on both nanotube , and GNR junctions , has suggested that junction conductance can be a sensitive function of nanoconductor overlap and that low junction conductance can severely limit carbon nanowire performance. Hence the effects of potassium doping on the GNR junction conductance, as a function of GNR overlap, are of central interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation